PENGETAHUAN LOKAL TENTANG LINGKUNGAN: STUDI KASUS ETNIS WAWONII, SULAWESI TENGGARA - Rahayu, Mulyati; Royyani, Mohammad Fathi; Rugayah, Rugayah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Wawonii ethnic represent the majority groups and ethnic origin dwelling Wawoniiisland, Southeast Sulawesi. In their traditional life, this ethnic has own mannersand customs for managing natural resources. Local knowledge researchÃ¢â‚¬â„¢s aboutenvironment ecosystem of owned Wawonii ethnic have been carried out since2003 to 2006. Several countryside of Wawolaa, Lansilowo, Lampeapi, Bobolioand Dompo-dompo Jaya have been visited during this study. At least 6 kindsenvironment sets have been identified, manely Ã¢â‚¬Å“kura eyaÃ¢â‚¬Â primary forest, Ã¢â‚¬Å“lalibataÃ¢â‚¬Â secondary forest, Ã¢â‚¬Å“anantaluÃ¢â‚¬Â brushes, Ã¢â‚¬Å“laro witaÃ¢â‚¬Â field, Ã¢â‚¬Å“laro leÃ¢â‚¬Â grasslandand Ã¢â‚¬Å“kapoÃ¢â‚¬Â village. Although there local knowledge have a lot of change, howeverit still remain their wisdom and become the guidance in their daily activities.